Low testosterone concentrations and prediction of future heart failure in men and in women: evidence from the large FINRISK97 study. (2nd May 2021) - Schäfer, Sarina; Aydin, Muhammet Ali; Appelbaum, Sebastian; Kuulasmaa, Kari; Palosaari, Tarja; Ojeda, Francisco; Blankenberg, Stefan; Jousilahti, Pekka; Salomaa, Veikko; Karakas, Mahir
Abstract: Aims: The increased incidence of heart failure in men suggests that endogenous sex hormones might play a role in the development of heart failure, but epidemiological data remain sparse. Here, we evaluated the predictive value of low testosterone levels on future heart failure in the large population‐based FINRISK97 study. Methods and results: Baseline serum testosterone concentrations were measured in 7855 subjects (3865 men and 3990 women) of the FINRISK97 study. During a median follow‐up (FU) of 13.8 years, a total of 564 heart failure events were recorded. The age‐adjusted baseline testosterone levels did not differ significantly between subjects developing incident heart failure during FU and those without incident events during FU (men: 16.6 vs. 17.1 nmol/L, P = 0.75; women: 1.15 vs. 1.17 nmol/L, P = 0.32). Relevant statistically significant correlations of testosterone levels were found with high‐density lipoprotein cholesterol levels ( R = 0.22; P < 0.001), body mass index ( R = −0.23; P < 0.001), and waist‐to‐hip ratio ( R = −0.21; P < 0.001) in men, while statistically significant correlations in women were negligible in effect size. In sex‐stratified Cox regression analyses, taking age into account, a quite strong association between low testosterone and incident heart failure was found in men [hazard ratio (HR) 1.51 (95% confidence interval, CI: 1.09–2.10); P = 0.020 for lowest vs. highest quarter], but not in women [HR 0.70 (95% CI: 0.49–0.98); P = 0.086 for lowest vs. highest quarter]. Nevertheless, this association turned non‐significant after full adjustment including body mass index and waist‐to‐hip ratio, and testosterone levels were no longer predictive for incident heart failure—neither in men [HR 0.99 (95% CI: 0.70–1.42); P = 0.77 for lowest vs. highest quarter] nor in women [HR 0.92 (95% CI: 0.64–1.33); P = 0.99 for lowest vs. highest quarter]. Accordingly, Kaplan–Meier analyses did not reveal significant association of testosterone levels with heart failure. Conclusions: Low levels of testosterone do not independently predict future heart failure.